Prediction of MAG Welding Formation Based on Fuzzy Interpolation Reasoning - Zufu Pan; Zhiqiang Feng; Hao Yuan; Xin Li (Applied Sciences, 2023)
Welding is an important production and processing method in industrial production. Due to the uncertainty of its process and the complexity of its mechanism, it is challenging to construct an accurate welding process parameter model to describe it. Fuzzy interpolation reasoning is a valuable tool in the realm of intelligent systems. It helps to reduce the complexity of fuzzy models and can be used for reasoning in fuzzy systems with sparse rule bases. This paper provides an interpolation reasoning method that combines fuzzy set distance and similarity. The proposed method is applied to welding forming predictions, and welding penetration is predicted by the given welding current and speed. The results show that the algorithm has high calculation accuracy.